Communication, culture and society : a Caribbean public information and communication policy (CCS GeorgetownGY, 1992)
Focuses on the need for a regional public communications and information policy. Examines the policy objectives and looks at the areas to be covered by the policy viz. - infocom technologies; infocom content; infocom processes; infocom structures.
Additional copy located in the Secretary-General's office